2019
DOI: 10.1016/j.copsyc.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The mindful family: a systemic approach to mindfulness, relational functioning, and somatic and mental health

Abstract: The mindful family: A systemic approach to mindfulness, relational functioning, and somatic and mental health One of these days I'll be over in a hospital somewhere with four walls around me. And the only people who'll be with me will be my family." -Robert Byrd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 38 publications
3
11
0
1
Order By: Relevance
“…Lastly, psycho-social health appeared to be higher for the groups that participated in leisure activities with others than people who participated in leisure activities alone. This aligns with the research by Bögels and Emerson [43] which showed that relationships with other people have an influence on individuals' physical and mental health. In particular, countermeasures like social distancing were reinforced, and people became more careful about maintaining relationships with others while practicing preventive behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, psycho-social health appeared to be higher for the groups that participated in leisure activities with others than people who participated in leisure activities alone. This aligns with the research by Bögels and Emerson [43] which showed that relationships with other people have an influence on individuals' physical and mental health. In particular, countermeasures like social distancing were reinforced, and people became more careful about maintaining relationships with others while practicing preventive behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with a growing literature on the relation between mindfulness and parental burnout [26,[52][53][54]. Indeed, mindfulness has been associated with lower levels of stress, anxiety, and depression among parents [43,55], with higher levels of emotion regulation [56], more effective conflict management [57], and, more generally, with better family relationships [58,59]. Furthermore, in accordance with our second hypothesis, mindfulness was shown to increase self-compassion [60] and decrease dysfunctional ruminations [61].…”
Section: Discussionsupporting
confidence: 90%
“…Encourage athletes to reach out to their best friends when seeking mental support and help them feel less isolated, since family members, trustworthy friends, and mentors are good places for people to turn to ( Bogels and Emerson, 2019 ).…”
Section: Resultsmentioning
confidence: 99%